2019
DOI: 10.2147/idr.s224545
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence Of <em>mcr-1</em> Among Cefotaxime-Resistant Commensal <em>Escherichia coli</em> In Residents Of Vietnam</p>

Abstract: PurposeThe dissemination of colistin-resistant bacteria harboring the colistin-resistance gene mcr-1 in developing countries has recently entered the spotlight as an emerging public health threat, which is attributed to the abuse of colistin use in these countries. However, the prevalence of these bacteria in developing countries has not been extensively investigated. Therefore, in the present study, we examined the prevalence of cefotaxime-resistant commensal Escherichia coli harboring mcr-1 among residents o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The chromosomal mcr-1-carrying bacteria may contribute to the emergence of untreatable MDR bacteria when MDR genes, including carbapenem resistance genes on the plasmid (14), are transferred to bacteria possessing chromosomal mcr. In fact, this likelihood is supported by our current study, wherein several extended-spectrum ␤-lactamase (ESBL)-producing E. coli isolates that had MDR with mcr-1 were obtained from fecal microbiota of healthy human residents of the community (15).…”
Section: Resultsmentioning
confidence: 62%
“…The chromosomal mcr-1-carrying bacteria may contribute to the emergence of untreatable MDR bacteria when MDR genes, including carbapenem resistance genes on the plasmid (14), are transferred to bacteria possessing chromosomal mcr. In fact, this likelihood is supported by our current study, wherein several extended-spectrum ␤-lactamase (ESBL)-producing E. coli isolates that had MDR with mcr-1 were obtained from fecal microbiota of healthy human residents of the community (15).…”
Section: Resultsmentioning
confidence: 62%
“…In this study, two IncI2 plasmids were obtained from the same farm, whereas the other five plasmids were respectively recovered from different farms. As a common mcr -disseminator, IncI2 plasmid was identified in isolates from animals, vegetables, and humans [ 49 , 54 , 55 ]. These results suggest that diversified conjugative plasmids, especially IncI2 plasmid, may be the key vectors that mediate the dissemination of the mcr-1 among Enterobacteriaceae [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…coli strains isolated from healthy residents during 2013–2016 in the Thai Binh Province of Vietnam showed that 6.9% of the ESBL-producing E . coli strains possessed mcr-1 [ 9 ]. Another study from the same area conducted during 2017–2018 showed that approximately 70% of healthy residents carried CR E .…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this hypothesis, Kawahara et al [8] reported that in a rural area of Vietnam, approximately 100% chicken and pig fecal samples contained CR Escherichia coli with mcr-1 or mcr-3. A retrospective study on extended-spectrum β-lactamase-(ESBL-) producing E. coli strains isolated from healthy residents during 2013-2016 in the Thai Binh Province of Vietnam showed that 6.9% of the ESBL-producing E. coli strains possessed mcr-1 [9]. Another study from the same area conducted during 2017-2018 showed that approximately 70% of healthy residents carried CR E. coli with mcr-1 and/or mcr-3, and that 92.8% of those isolates were multidrug resistant [10].…”
Section: Introductionmentioning
confidence: 99%